[Polacsek 1]
1942 young lady walk the dog meets other lady, Budapest streets, boy&dog, 1939 Zoo, Polacsek himself, 1942 Budapest International Fair, young lady on the streets, swimming-pool Gellért, other ladies, 1940 skating Heroes Square, winter in Budapest, holiday in Garámkövesd, village scenes, City park, neon signs,